Factors Influencing Dividend Payout in Manufacturing Industries Listed on the Indonesia Stock Exchange - Rudy*, Ryan Pahlawan; Hady, Hamdy; Nalurita, Febria (Universitas Syiah Kuala, 2023)
This study aims to examine the influence between return on assets, firm size, liquidity, financial leverage, investment opportunity, and company growth on dividend payout The data in this study are quantitative data, namely the annual reports of manufacturing companies available on the Indonesia Stock Exchange website (www.idx.co.id) and the official website of each company, for 6 years (2017-2022). The sample withdrawal method used in this study was purposive sampling so that 22 companies were sampled. The data analysis used to test the hypothesis is panel data regression analysis using the Eviews 10.0 program. Based on the research results that have been obtained, it is known that return on assets, leverage, and company growth have a negative and significant effect, while firm size, financial leverage, and investment opportunity have no effect on dividend payout. To increase dividend payout, companies should be able to manage ROA properly and efficiently by considering the proportion of retained earnings to remain maximum in generating capital gains, in addition to being able to maximize the effectiveness of fixed assets in addition to low current assets so that the added value of the products produced by the company is more optimal, so that it will increase profits, companies that are growing significantly are expected to utilize their internal finances well so that internal and external funding sources can generate optimal profits. This research should be used by investors in Indonesia and abroad in their investment activities in manufacturing companies in Indonesia. In order for the investment made to bring big profits.